Management of Major Engine Maintenance and Repair Strategy at KM Thalia to Improve Ship Operational Efficiency - Jainuddin, Jainuddin (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
Maintenance and repair of the ship's main engine is a crucial aspect in ensuring that ship operations remain optimal and efficient. This study aims to analyze the maintenance and repair methods of the main engine in KM Thalia and the impact that can arise due to errors in its maintenance. This study uses a qualitative approach with primary data obtained through direct observation and interviews with the ship's crew. The results of the study show that effective maintenance methods include preventive, predictive, corrective, and breakdown maintenance. Errors in maintenance can lead to machine failure, increased operating costs, and significant safety risks. By implementing the right maintenance strategy, the life of the engine can be extended and the performance of the vessel remains optimal. This study emphasizes the importance of a maintenance management system based on international safety standards to improve ship operational efficiency.Keywords: Ship maintenance, main engine repair, operational efficiency, safety management.